2016
DOI: 10.1212/wnl.0000000000003044
|View full text |Cite
|
Sign up to set email alerts
|

GABA deficiency in NF1

Abstract: Objective:To provide a comprehensive investigation of the γ-aminobutyric acid (GABA) system in patients with neurofibromatosis type 1 (NF1) that allows understanding the nature of the GABA imbalance in humans at pre- and postsynaptic levels.Methods:In this cross-sectional study, we employed multimodal imaging and spectroscopy measures to investigate GABA type A (GABAA) receptor binding, using [11C]-flumazenil PET, and GABA concentration, using magnetic resonance spectroscopy (MRS). Fourteen adult patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…These results somewhat contradict those of Rodrigues et al (40), who found a preservation of NAA values but an increase in MyoInositol/Creatinine and Choline/Creatinine ratios in the basal ganglia with the use of a larger sample (42 NF1 subjects aged 4 to 24 years and 25 healthy controls) regardless of the UBOs status (presence or absence). Lastly, Violante et al (41) used magnetic resonance spectroscopy (MRS) and [11C]-flumazenil PET, to compare 14 NF1 adults and 13 matched controls. These authors found a lower gamma-aminobutyric acid (GABA) concentration in the visual cortex and the frontal eye fields (FEF) (11.5 and 22% respectively), and a reduction in the binding of GABA A receptors in the left parieto-occipital cortex, midbrain and thalami, which were not explained by a lower GM volume.…”
Section: Multimodal Approachmentioning
confidence: 99%
“…These results somewhat contradict those of Rodrigues et al (40), who found a preservation of NAA values but an increase in MyoInositol/Creatinine and Choline/Creatinine ratios in the basal ganglia with the use of a larger sample (42 NF1 subjects aged 4 to 24 years and 25 healthy controls) regardless of the UBOs status (presence or absence). Lastly, Violante et al (41) used magnetic resonance spectroscopy (MRS) and [11C]-flumazenil PET, to compare 14 NF1 adults and 13 matched controls. These authors found a lower gamma-aminobutyric acid (GABA) concentration in the visual cortex and the frontal eye fields (FEF) (11.5 and 22% respectively), and a reduction in the binding of GABA A receptors in the left parieto-occipital cortex, midbrain and thalami, which were not explained by a lower GM volume.…”
Section: Multimodal Approachmentioning
confidence: 99%
“…In humans, we have found that excitation/inhibition balance is altered in the visual and medial frontal cortex of patients with NF1, as a consequence of reduced GABA concentration [ 13 , 14 ]. More recently, we observed a decreased binding of GABA(A) receptors (GABA(A)R) in patients in the parieto-occipital cortex, midbrain, and thalamus suggesting neurodevelopmental synaptopathy both at the pre- and postsynaptic level [ 15 , 16 ]. However, levels of GABA and GABA(A)R have never been assessed in NF1 mutant mice, which is important to link the preclinical model to clinical observations and to the development of therapies targeting GABAergic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the link between GABA and hemodynamic response, as measured by the BOLD signal, is complex. GABA concentration has been shown to be reduced in patients with NF1 (47), and more research is warranted to determine how this may play a role in the BOLD response in patients with NF1 (48). …”
Section: Discussionmentioning
confidence: 99%